PENGARUH SENAM AEROBIK LOW IMPACT TERHADAP PENURUNAN TEKANAN DARAH DI PUSKESMAS PADANG SELASA - Dayanah; Nurjannah (Jurnal Kesehatan dan Pembangunan, 2026)
Linguistically, "dewasa" comes from the Latin word "adultus," which means "to grow into perfect strength and size or to have become mature." In terms of terminology, an adult is an individual who has reached their developmental stage and is ready to participate in society alongside other adults. The purpose of the research is to determine the effect of low-impact aerobic exercise on lowering blood pressure in hypertensive patients. The research method uses a Pre-Experimental design with a one group pre post test design. The population in this study consists of all adult age groups at the Puskesmas Padang Selasa Palembang, with a sample size of 35 respondents. The sampling was conducted using the purposive sampling technique. The research results showed that there is an effect of low-impact aerobic exercise on systolic blood pressure (p.value = 0.001), the effect of low impact aerobics on diastolic blood pressure (p.value = 0.012) in reducing blood pressure. It is hoped that the recommendation can provide non-pharmacological treatment to reduce blood pressure in adults independently at home, in addition to pharmacological treatment.